Simulation of magnetic resonance for wireless power transfer - Zhao, Liang (2015)
André Kurs et al. et al. (2007) in Science 317, 83 titled Wireless Power Transfer via Strongly Coupled Magnetic Resonances, proposed a feasible scheme to near-field transfer electric energy. Here in this report we take note of our simulation on COMSOL 4.1.085 to repeat his counterpart in Chapter 4 of his master thesis. Due to huge requirement on memory size, my simulation fails to align with Kurs', but basic steps and setup instructions are given. Very importantly, every scholar with electromagnetic background would simply take this as magnetic inducing current in closed loops, exactly as we did. Yet, this imparts more essence on resonance. A look into coupled-mode theory will find this takes advantage of near-field magnetic field to transfer energy. A transformer, a true product of magnetic induction, if simply detached by a distance would greatly reduce its transfer efficiency, whereas magnetic resonance DOES NOT! So this is more than only magnetic induction. Although coupled-mode theory is still not physical enough to illustrate readers, neither does magnetic induction in Maxwell's equations give its simple picture! Coupled-mode theory perhaps is a simple way out quantitatively and mathematically.